2017
DOI: 10.3928/24748307-20170808-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Is an Independent Predictor of Cancer Patients' Hospitalizations

Abstract: Background: Lower levels of health literacy predict higher hospitalization rates. Hospitalization is expensive and many admissions are potentially avoidable. Research examining the relationship between health literacy and health outcomes for cancer patients is limited, and no published studies to date have focused on hospitalization and health literacy in cancer patients. Objective: This study examined the ability of health literacy to predict hospitalization of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
0
29
1
2
Order By: Relevance
“…This is in line with findings from Belgium, which also show no relationship between HL and emergency consultations (Vandenbosch et al, 2016). However, our results contradict findings from Italy (Palumbo et al, 2016) and the U.S. (Berkman et al 2011; Cartwright et al, 2017; Griffey et al, 2014), which show an independent, direct relation between HL and emergency service and hospital use.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in line with findings from Belgium, which also show no relationship between HL and emergency consultations (Vandenbosch et al, 2016). However, our results contradict findings from Italy (Palumbo et al, 2016) and the U.S. (Berkman et al 2011; Cartwright et al, 2017; Griffey et al, 2014), which show an independent, direct relation between HL and emergency service and hospital use.…”
Section: Discussioncontrasting
confidence: 99%
“…Patient studies in the U.S. indicate that HL is related to health service use, health status indicators, and health behavior. People with lower functional HL are less likely to use preventive services and more likely to use and repeatedly use emergency or hospital care (Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011; Cartwright, Dumenci, Cassel, Thomson, & Matsuyama, 2017; Griffey, Kennedy, D'Agostino McGowan, Goodman, & Kaphingst, 2014; Michtell, Sadikova, Jack, & Paasche-Orlow, 2012; Scott, Gazmararian, Williams, & Baker, 2002).…”
Section: Health Literacy and Health Outcomesmentioning
confidence: 99%
“…Bemerkenswert sind auch die Befunde zum Outcome von Health Literacy. Sie sprechen dafür, dass eine hohe Gesundheitskompetenz Hand in Hand mit einer höheren Teilnahme an gesundheitsförderlichen und präventiven Maßnahmen geht [5,6] und außerdem mit einem gesünderen Lebensstil, besserer Ernährung, höherer körperlicher Aktivität und geringerer Nutzung von Versorgungsangeboten wie Notfallambulanzen oder Arztpraxen korreliert [5,[7][8][9].…”
Section: Erarbeitung Des Nationalen Aktionsplansunclassified
“…HL as an entity is more important in functioning as a patient with cancer because interactions with varied specialties for surgery, radiation, cycles of chemotherapy, and post-treatment care are complex [5]. Corroborating with this, Cartwright et al [6] also concluded in their study that HL is an independent predictor of hospital admissions in cancer patients. Another meta-analysis of Adverse Drug Reactions (ADRs) in hospitalized patients by Lazarou et al [7] found anti-cancer drugs to be the main contributor to deaths related to ADRs.…”
Section: Introductionmentioning
confidence: 97%